2010
DOI: 10.1186/1471-2164-11-552
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide SNP-association study confirms a sequence variant (g.66493737C>T) in the equine myostatin (MSTN) gene as the most powerful predictor of optimum racing distance for Thoroughbred racehorses

Abstract: BackgroundThoroughbred horses have been selected for traits contributing to speed and stamina for centuries. It is widely recognized that inherited variation in physical and physiological characteristics is responsible for variation in individual aptitude for race distance, and that muscle phenotypes in particular are important.ResultsA genome-wide SNP-association study for optimum racing distance was performed using the EquineSNP50 Bead Chip genotyping array in a cohort of n = 118 elite Thoroughbred racehorse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
156
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 33 publications
4
156
1
5
Order By: Relevance
“…The 47 SNP-haplotypes (Fig. 1a) spanned the 1.9-Mb region at the MSTN gene locus that contained a set of eight SNPs with genome-wide significance of association with best race distance in a previous genome-wide association study 20 . The C-allele was observed on a single haplotypic background spanning 932 kb (that is, no variation was detected between BIEC2-417299 and BIEC-417453; ECA18: 66064660-66996871 bp; n = 17 SNPs that were present at MAF > 0.05 in Thoroughbreds; Supplementary Data 1, TB_C1) and only minimal variation was detected in a single proximal region (Block 1) upstream of the g.66493737C/T SNP (Fig.…”
Section: Genetic Ancestry and Geographic Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 47 SNP-haplotypes (Fig. 1a) spanned the 1.9-Mb region at the MSTN gene locus that contained a set of eight SNPs with genome-wide significance of association with best race distance in a previous genome-wide association study 20 . The C-allele was observed on a single haplotypic background spanning 932 kb (that is, no variation was detected between BIEC2-417299 and BIEC-417453; ECA18: 66064660-66996871 bp; n = 17 SNPs that were present at MAF > 0.05 in Thoroughbreds; Supplementary Data 1, TB_C1) and only minimal variation was detected in a single proximal region (Block 1) upstream of the g.66493737C/T SNP (Fig.…”
Section: Genetic Ancestry and Geographic Distributionmentioning
confidence: 99%
“…Evaluation of retrospective racecourse performance, physical growth and stallion progeny performance has demonstrated that C/C and C/T horses are more likely to be physically precocious and enjoy greater racecourse success as 2-year-old racehorses than T/T horses 19,28 . These findings have been subsequently validated in three independent genome-wide association (GWA) studies 18,20,21 in populations of Thoroughbreds originating in Ireland, Great Britain, New Zealand 20 , USA 18 and Japan 21 . The singular, genomic influence on optimum race distance at the MSTN locus in the Thoroughbred is supported by a high heritability for race distance (h 2 = 0.94) 29 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results of the qualitative trait GWAS demonstrated that the sample size used was sufficient to detect a major genetic effect such as that manifested at the ASIP locus. As reported in earlier studies of population isolates (for example, Peltonen et al, 2000;Hill et al, 2010), the high levels of LD in the isolated Finnsheep population are a reflection of low effective population size, which enables detection of association with smaller sample sizes. However, in the analysis of only non-white colours that include less than half of the animals, the power of the test could be relatively low, and thus contributes partly to the lack of significant associations (see for example, Han et al, 2008;Hill et al, 2010).…”
Section: Asip As a Candidate Gene For White Versus Non-whitementioning
confidence: 74%